1992
DOI: 10.1142/s0218216592000203
|View full text |Cite
|
Sign up to set email alerts
|

Racks and Links in Codimension Two

Abstract: A rack, which is the algebraic distillation of two of the Reidemeister moves, is a set with a binary operation such that right multiplication is an automorphism. Any codimension two link has a fundamental rack which contains more information than the fundamental group. Racks provide an elegant and complete algebraic framework in which to study links and knots in 3–manifolds, and also for the 3–manifolds themselves. Racks have been studied by several previous authors and have been called a variety of names. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
549
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 392 publications
(562 citation statements)
references
References 0 publications
8
549
0
Order By: Relevance
“…This definition of colorings on knot diagrams has been known, see [13,17] for example. Henceforth, all the quandles that are used to color diagrams will be finite.…”
Section: Introductionmentioning
confidence: 99%
“…This definition of colorings on knot diagrams has been known, see [13,17] for example. Henceforth, all the quandles that are used to color diagrams will be finite.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], David Joyce showed that racks are indeed a knot invariant. Subsequently, Fenn and Rourke introduced racks as proper knot invariants in [3]. It is instructive to consider racks as groups without their multiplicative elements.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…A quandle (see Fenn and Rourke [3], Joyce [5] or Matveev [10]) is a set X with a binary operation .x; y/ 7 ! x y such that (i) for any x 2 X , it holds that x x D x , (ii) for any x; y 2 X , there exists a unique z 2 X such that z y D x , and (iii) for any x; y; z 2 X , it holds that .x y / z D .x z / .y z / .…”
Section: Symmetric Quandles and Their Cocyclesmentioning
confidence: 99%